Evaluation Of Risk-Based Leadership Systems, Communication Systems, And Decision-Making Processes To Improve Project Time Performance In Indonesian Construction MSME Contractors - Fadhil Ahmad Rusydi; Yusuf Latief (CV. AFDIFAL MAJU BERKAH, 2026)
The construction service industry at the Micro, Small, and Medium Enterprise (MSME) level in Indonesia plays an important role in supporting national development. However, MSME construction companies still face various challenges in achieving project time performance. Project delays in MSME construction companies are generally influenced by weak leadership systems, ineffective communication systems, and suboptimal decision-making processes during project implementation. Therefore, this study aims to analyze the influence of leadership systems, communication systems, and decision-making processes on project time performance, as well as to develop a relationship model among these variables in MSME construction service companies in Indonesia. This study employed a quantitative approach using a survey method through questionnaire distribution to MSME construction service companies in Indonesia. Data analysis was conducted using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method to examine the relationships among the research variables. The independent variables in this study consist of leadership systems, communication systems, and decision-making processes, while the dependent variable is project time performance. The results indicate that leadership systems, communication systems, and decisionmaking processes have a positive and significant effect on project time performance in MSME construction service companies. The communication system was identified as the most dominant variable in improving work coordination, accelerating project information delivery, and reducing the potential for project delays in the field. This study also produced a structural relationship model describing the interaction between leadership systems, communication systems, and decision-making processes in improvingconstruction project time performance within MSME companies. The resulting model demonstrates that the implementation of effective leadership systems, supported by effective communication systems and fast and accurate decision-making processes, can improve the timeliness of construction project completion. The novelty of this study lies in the development of an integrative model that simultaneously connects leadership systems, communication systems, and decisionmaking processes within the context of MSME construction service companies in Indonesia, which remains relatively underexplored in previous studies. This research is expected to serve as a reference for MSME construction companies in improving project performance, particularly in terms of project time performance